Analysis of vehicle parameters for flow technology of fruit harvesting (Science journal «Technical service of agriculture, forestry and transport systems», 2026)
The article reveals the features of the methodological justification of vehicle parameters for flow technology of fruit harvesting. Balanced development of all links of the agro-industrial complex is a necessary condition for providing the country with food, in particular fruit and vegetable raw materials. Currently, the weak development of the processing branches of the agro-industrial complex, the production infrastructure of the complex lead to significant losses of agricultural products. Thus, losses of harvested fruits and vegetables are 40-45%. The need for vehicles for gardening and vegetable growing is satisfied only by 55-60%. One of the most significant and complex tasks is to reduce damage and losses of agricultural products, where a responsible role is assigned to vehicles. As the analysis showed, in the process of harvesting apples, more than 15-20% of the products do not reach the consumer. For intra-farm transportation of fruits, boxes or containers are used. Fruits of pome crops are transported in bulk (in car bodies and tractor trailers). The use of general-purpose vehicles does not meet the agrotechnical requirements for transporting fruits, and there are no special vehicles for transporting fruits in bulk. The feasibility of using special storage containers for the flow technology of fruit harvesting is outlined, and their main parameters are substantiated, including optimal load capacity.
Keywords: fruits; technology; transportation; mechanical damage; load capacity